Phytochemical study of Uncaria longiflora variety pteropoda / Nur Shafiqah Adilah Ahmad Zawawi - Ahmad Zawawi, Nur Shafiqah Adilah (Faculty of Applied Sciences, 2010)
The local name of Uncaria longiflora variety pteropoda is 'kekaif. This plant contains high medicinal value. The non-alkaloids of Malaysian Uncaria longiflora variety pteropoda stems extract were isolated and their structures were elucidated. The dried non-acidified extract of Uncaria longiflora variety pteropoda stems was fractionated using vacuum liquid chromatography before being introduced to column chromatography and preparative thin layer chromatography to yield three sterols, UL-T1, UL-T2, and UL-T3. ¹H NMR spectroscopy was used in determining the structures of sterols isolated. The compounds were identified as stigmast-5,22-dien-3-ol, stigmast-22-en-3-ol, and cholest-4-en-6α-ol-3-one.